Examining Recovery Status Trends over 7-Years for Men and Women Clients of a Substance Use Disorder Recovery Housing Program - Logan, TK (Journal of drug issues, 2022)
Adults who are homeless and/or involved in the criminal justice system have significantly higher risks of substance use disorders (SUD)s and they may have increased difficulty initiating and maintaining traditional SUD treatments. To address the needs of adults with SUDs who are homeless/criminal justice system involved the Recovery Kentucky programs were established. This study examined outcomes for this recovery housing program among an unduplicated statewide sample of men (n=672) and women (n = 732) clients who entered the Recovery Kentucky program and who were followed-up about 12 months after program entry across a 7-year period. Low, but similar rates of problem alcohol or illicit drug use at follow-up were found across the 7-year period. Men had higher rates of return to use than women. Further, about 40% of the clients had at least one recovery status vulnerability factor at follow-up each year of the study with no differences by gender.